An exploratory research on performance improvement of super-large natural draft wet cooling tower based on the reconstructed dry-wet hybrid rain zone, part 2: Crosswind effects. (October 2020) - Zhang, Zhengqing; Wang, Mingyong; Liu, Yang; Gao, Ming; He, Suoying; Shi, Yuetao
Highlights: Investigations on dry-wet rain zone under crosswind conditions are proposed. Water temperature drop increases by about 0.4°C on average for the dry-wet rain zone. The effects of crosswind angle and velocity on performance of NDWCT are studied. Effects of the crosswind velocity are far greater than that of the crosswind angle. Abstract: To enhance the performance of the super-large natural draft wet cooling towers (S-NDWCTs), and finally to achieve the goal of energy-saving in thermal systems, the dry-wet hybrid rain zone was proposed in our previous paper. However, the previous work failed to discuss the effects of crosswind which are extremely significant for the research for S-NDWCTs. Therefore, the thermal and aerodynamic performances of the cooling tower are investigated for variation crosswind speeds (0 m/s ~ 16 m/s) and crosswind angles (0° ~ 45°) by numerical method. The results show that the airflow and circulating water temperature distributions in the dry-wet tower are more uniform than those in the usual tower within the range of studied crosswind velocities; The water temperature drop raises by about 0.40°C on average within the studied crosswind speed range; For the dry-wet rain zone tower, while the environment wind speed raises from 2 to 4 m/s, the water temperature drop decreases by 0.63°C, the ventilation rate decreases by 9.5%, the Merkel number decreases by 0.17; The influences of changing crosswind angle on the performance of wet cooling tower are not obvious.